Features of the development of strength training of highly qualified football referees in the competitive period - Anatoliy Abdula; Andrii Pertsukhov; Krzysztof Wnorowski; Svitlana Mozharovska; Yuriy Mozharovskyy (Kharkiv State Academy of Physical Culture, 2022)
Purpose: to identify the features of the development of strength training of highly qualified football referees in the competitive period. Material & Methods: the study involved 30 highly qualified football referees aged 35-42: 4 FIFA referees, 15 Premier League referees and 11 First League referees. Results: the training program for strength development in the competitive period included new fitness training tools using TRX® functional loops, step platform, BOSU hemisphere, 6D sliding. In the preparatory and final part of the training session, we included MFR exercises to fill the muscles with the maximum volume of blood and activate the nerve centers for their additional stretching. The results of testing the physical fitness of highly qualified referees at the beginning and end of the competitive period indicate that the training program developed by us, aimed at developing strength in competitive microcycles, most significantly influenced the increase in the manifestation of strength qualities in flexion and extension of the arms in emphasis. 8% and speed endurance in the YO-YO test - by 15,1%. There was also an improvement in the results in the manifestations of speed by 7.4% and by 2.3% in the 40 m run and the 4x10 m shuttle run, as well as by 5,7% in the speed-strength abilities in the standing long jump test. Conclusions: the results of the study indicate the effectiveness of the strength training program for referees of different levels and qualifications and its use in training microcycles of the competitive period to improve physical fitness.